2016
DOI: 10.1590/0034-737x201663030001
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo in vitro da bananeira Prata Anã clone Gorutuba, em meio líquido, agitado e estacionário

Abstract: RESUMO O objetivo deste trabalho foi avaliar o cultivo in vitro da bananeira Prata Anã (Musa spp.), clone Gorutuba, em diferentes volumes de meio líquido, nos sistemas estacionário e sob agitação, comparando-os com o cultivo tradicional em meio semissólido. O experimento foi conduzido em delineamento inteiramente casualizado, sendo um fatorial 5 x 2 + 1, com cinco volumes (10, 15, 20, 25 e 30 mL) de meio líquido e dois sistemas de cultivo (agitação e estacionário) e a testemunha (meio semissólido), com quatro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…The efficacy of liquid culture systems, specifically temporary immersion systems, has also been demonstrated. The liquid medium had a strong influence on the development and multiplication rate of micropropagated banana plants compared to that in conventional growth on a semisolid medium (Alvard et al, 1993;Etienne et al, 1999;Costa et al, 2016). This was demonstrated in this study, as most growth characteristics of the banana plants were higher in the liquid medium than in the solid medium (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The efficacy of liquid culture systems, specifically temporary immersion systems, has also been demonstrated. The liquid medium had a strong influence on the development and multiplication rate of micropropagated banana plants compared to that in conventional growth on a semisolid medium (Alvard et al, 1993;Etienne et al, 1999;Costa et al, 2016). This was demonstrated in this study, as most growth characteristics of the banana plants were higher in the liquid medium than in the solid medium (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 61%
“…Lemos et al (2001) showed that liquid media in both permanent and temporary immersion bioreactor systems increase the contact area of the explant with the media, which favors greater absorption of nutrients and water by in vitro tissues and organs. In similar studies, liquid media that were either stationary (Costa, Faria, Londe, Ribeiro, & Damascena, 2016;Siqueira, Santos, Salomão, Silva, & Barros, 2013) or agitated (Costa et al, 2016) promoted increased pseudostem diameter, leaf number, and fresh mass of in vitro banana shoots compared to those in semisolid media. There was a significant interaction between the addition of Si and the type of culture system, whereby Si contributed to increased plant DW in the liquid culture system (TIS bioreactor).…”
Section: Resultsmentioning
confidence: 85%